How and when do Pt- and Pd-semimetal minerals crystallize from saturated sulfide liquids? - Helmy, Hassan M.; Botcharnikov, Roman; Ballhaus, Chris; Buhre, Stephan (Frontiers in Earth Science, 2024)
Abstract Platinum and Pd-arsenides, antimonides, tellurides, bismuthinides and sulfides are the major host of Pt and Pd in magmatic and hydrothermal Cu-Ni-sulfide ores. Textural relationships among such minerals in nature often provide contradictory messages about the mechanism and timing of their formation. To know how and when Pt and Pd mineral phases crystallize from sulfide-saturated liquids and how their compositions and textures evolve during cooling we undertook controlled cooling experiments in evacuated silica tubes. A Cu-Ni-Fe sulfide mixture, similar in composition to the average Merensky Reef sulfide magma, was charged (in 9:1 wt.% proportion) with one of the PtAs2, PtTe2, PtSb2, PtBi2, PdAs2, PdTe2, PdSb and PdBi2 compounds, heated to 1100 °C and slowly cooled (15 °C/day) to room temperature. The run products were sampled at 950, 750 and 25 °C by quenching the silica tubes in water. The results show that Pt formed stable phases with As, Te and Sb above 950 °C and with Bi and S below 750 °C. The Pt phases were found mostly in the decomposed intermediate solid solution (ISS) and all the phases survived to 25 °C with no compositional changes. At 950 °C, Pd formed arsenide, telluride and antimonide immiscible melts that coexisted with monosulfide solid solution (MSS) and sulfide melt. The composition of the Pd-semimetal melt droplets changed during cooling by equilibration with the host sulfide. Palladium mineral phases formed at temperatures below 750 °C directly from the immiscible semimetal-rich melts where they kept the rounded shapes of the melt droplets. Ni-sulfarsenides preceded the formation of Pd arsenides. No Ni tellurides, antimonides or bismuthinides formed in any of the systems, implying that their formation requires higher semimetal/Pt+Pd ratios. The decomposition of MSS and ISS to base metal sulfides led to significant textural changes of Pt and Pd mineral grains. The compositions of Pt and Pd phases are inherited from the magmatic stage, while their textures are low-temperature (< 450 °C) features.